1979
DOI: 10.1111/j.2044-8279.1979.tb02396.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐cultural Study of Science Classroom Interactions

Abstract: Summary. A British observational study of science classroom interactions was replicated in Atlantic Canada with 33 teacher‐class units. Observational data from the Canadian classrooms were cluster‐analysed and two preferred teaching styles emerged from this analysis. It was concluded that patterns of teaching in the Canadian classrooms studied differed substantially from those patterns observed in classrooms in the United Kingdom. An overall comparison of the results of the two studies revealed a less practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The enquiries referred to here, which span almost a decade, focused on science teaching in secondary schools and stem from the construction of a Science Teaching Observation Schedule [1]. Although this schedule was designed for use with experienced teachers in English schools it has subsequently been used in Canadian [2], Australian [3] and Indian schools, and its use has been extended to studentteachers of sciences. This system was the outcome of an essentially reductionist attempt to monitor classroom interactions in order to facilitate comparison between teachers and the construction of typologies based on the kinds and frequencies of intellectual transactions which were observed.…”
Section: Jim Eggleston University Of Nottinghammentioning
confidence: 99%
“…The enquiries referred to here, which span almost a decade, focused on science teaching in secondary schools and stem from the construction of a Science Teaching Observation Schedule [1]. Although this schedule was designed for use with experienced teachers in English schools it has subsequently been used in Canadian [2], Australian [3] and Indian schools, and its use has been extended to studentteachers of sciences. This system was the outcome of an essentially reductionist attempt to monitor classroom interactions in order to facilitate comparison between teachers and the construction of typologies based on the kinds and frequencies of intellectual transactions which were observed.…”
Section: Jim Eggleston University Of Nottinghammentioning
confidence: 99%
“…The subjects were junior secondary science teachers in the Ciskei, South Africa. The instrument STOS was developed in the early 1970's for use in the evaluation of Nuffield science materials in England, but has also been used in a number of other situations (Hacker et al, 1979, Dreyfus and Eggleston, 1979, Keiny and Jungwirth, 1982, Hinton, 1985.…”
Section: Observations Of Science Teaching Elsewherementioning
confidence: 99%
“…In a study carried out in Canadian grade nine classes using STOS, Hacker et al (1979) found that two clusters emerged from the analysis. Style A, described as "didactic, teacher-directed and theoretical" (p. 56), was favored by biology teachers and covered only a few STOS categories.…”
Section: Observations Of Science Teaching Elsewherementioning
confidence: 99%
“…The work has as practical bias, and the level of intellectual engagement is high. This typology was validated by replication with matched samples of teacherclass units in Canada (Hacker et al 1979), and in Australia (Hacker and Miles 1980), where similar profiles were found. These findings provided support for Eggleston's (1980) assertion that the effects of the shared culture of science transcends social differences to determine the ways teachers and pupils behave with respect to intellectual transactions.…”
Section: Introductionmentioning
confidence: 81%